2017
DOI: 10.3233/ajw-170041
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting of PM10 Using Autoregressive Models and Exponential Smoothing Technique

Abstract: Particulate matter with 10 μm or less in diameter (PM 10 ) have adverse effects on environment and human health. To reduce PM 10 emissions in India, it is essential to have models that accurately estimate and predict PM 10 concentrations for reporting and monitoring purposes. In this paper Exponential Smoothing Technique and Autoregressive (AR) models are developed to forecast 1-month ahead value of PM 10 for Allahabad city which is novelty of this study. AR (1) and AR (5) models are developed using Burge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…The MAPE value, which is frequently used by researchers to evaluate ANN model performances, is expected to be below 10% (Antanasijević et al 2013;Tiryaki et al 2016). It has been demonstrated that the prediction performance of ANN models is high with these values lower than 10% (Yadav and Nath 2017). It is stated in the literature that it is extremely important to calculate RMSE values as well as MAPE values in order to determine the performance of prediction models (Kucukonder et al 2016).…”
Section: Experimental and Ann Analysis Resultsmentioning
confidence: 99%
“…The MAPE value, which is frequently used by researchers to evaluate ANN model performances, is expected to be below 10% (Antanasijević et al 2013;Tiryaki et al 2016). It has been demonstrated that the prediction performance of ANN models is high with these values lower than 10% (Yadav and Nath 2017). It is stated in the literature that it is extremely important to calculate RMSE values as well as MAPE values in order to determine the performance of prediction models (Kucukonder et al 2016).…”
Section: Experimental and Ann Analysis Resultsmentioning
confidence: 99%
“…The MAPE values were 2.856% for the training set and 8.556% for the testing set. Several researchers reported that model performance is accepted as excellent if MAPE ≤ 10% (Chang et al 2007, Aydin et al 2014, Yadav and Nath 2017. Accordingly, the prediction ability of the ANN model can be accepted as excellent since its MAPE value is lower from 10%.…”
Section: Resultsmentioning
confidence: 99%
“…MAPE, en önemli değerlendirme kriterlerinden biridir ve birçok araştırmacı, MAPE'yi kullanarak model performansını değerlendirmiştir (Antanasijević et al, 2013;Tiryaki et al, 2016, Yadav & Nath, 2017. Literatürde MAPE değerinin%10'un altında olması durumunda model performansının yüksek olduğu belirtilmiştir (Yadav & Nath, 2017).…”
Section: Veri Toplamaunclassified
“…MAPE, en önemli değerlendirme kriterlerinden biridir ve birçok araştırmacı, MAPE'yi kullanarak model performansını değerlendirmiştir (Antanasijević et al, 2013;Tiryaki et al, 2016, Yadav & Nath, 2017. Literatürde MAPE değerinin%10'un altında olması durumunda model performansının yüksek olduğu belirtilmiştir (Yadav & Nath, 2017). Bu çalışmada, retensiyon miktarına ait MAPE değerleri, eğitim verileri için %1.630 ve test verileri için %4.372 olarak hesaplanırken, formaldehit emisyon değerlerine ait MAPE değerleri, sırasıyla %0.891 ve %3.529 olarak belirlenmiştir (Tablo 1 ve 2).…”
Section: Veri Toplamaunclassified